Beat-to-beat coronary wave intensity analysis: implications of backward waves originating from microvascular - Xie, Xinzhou; Han, Peng; Yu, Tiantong; Huang, Zixi; Lin, Heqiang; Xie, Songyun; Zhang, Bohui; Zhao, Shuai; Wang, Che; Li, Chengxiang; Chen, Yan; Lian, Kun (Frontiers in Cardiovascular Medicine, 2025)
IntroductionWhile coronary wave intensity analysis (cWIA) offers a promising way to assess myocardial and microvascular function by decomposing microvascular-originated backward waves, its clinical utility is currently limited by complex data acquisition and unclear influence of varying hemodynamic factors (adenosine, stenosis and vessel type).MethodsThis study introduces an angiography-based cWIA method and clarifies how those hemodynamic factors impact cWIA parameters. This retrospective study included 124 patients with 125 target vessels, for which beat-to-beat cWIA was successfully performed at rest and during adenosine-induced hyperemia.ResultsOur analysis revealed a strong and significant correlation between cumulative backward compression wave intensity (cBCW) and cumulative backward decompression wave intensity (cBDW) in both resting (rho = 0.846, 95%CI: 0.786 to 0.891, p < 0.001) and hyperemic states (rho = 0.768, 95%CI: 0.681 to 0.833, p < 0.001). Compared to rest, adenosine-induced hyperemia significantly increased cBCW (1.88 ± 1.46 ×104 W/m2s vs. 2.31 ± 1.74 × 104 W/m2s, p < 0.001) and peak backward compression wave intensity (pBCW) (4.30 ± 4.61 ×105 W/m2s2 vs. 5.21 ± 4.68 × 105 W/m2s2, p = 0.008), while significantly decreasing peak backward decompression wave intensity (pBDW) (5.41 ± 6.06 × 105 W/m2s2 vs. 3.99 ± 4.64 × 105 W/m2s2, p < 0.001), with no significant effect on cBDW. Neither functional stenotic lesions nor vessel type [left anterior descending coronary artery (LAD) or right coronary artery (RCA)] significantly impacted quantitative parameters of the microvascular-originated backward waves.DiscussionThe clinical feasibility of a convenient cWIA method was validated, and the impact of various hemodynamic factors on quantitative parameters of cWIA were analyzed, providing strong support for the clinical application of cWIA.